Synthesis and application of functionalized Graphene oxide-silica with chitosan for removal of Cd II fromaqueous solution - Azizkhani, Sepehr; Hussain, Siti Aslina; Abdullah, Norhafizah; Shah Ismail, Mohd Halim; Mohammad, Abdul Wahab (Springer, 2021)
The functionalized graphene oxide by silica and chitosan helped to prepared an adsorbent with high adsorption potential for removing cadmium(II). In this study, the adsorbent was synthesized and the batch system of adsorption method was examined to find the potential of the new adsorbent with the various factors of the concentration, pH, time and temperature. The characterization of adsorbent was analyzed by FT-IR, TEM, Zeta potential and XRD analysis. Regards to the analysis it can be understood that the adsorbent was synthesized successfully. The investigational results were validated and analyzed by applying the 5 models of isotherm and 4 models of kinetic. The Langmuir, Freundlich, Temkin, Harkins-Jura and Dubinin-radushkevich models were used which the Langmuir, Freundlich and Temkin fitted well for removing cadmium(II). The Qmax value was achieved 126.58 mg/g by using the Langmuir model for removing Cd(II) respectively. The pseudo-first-order, pseudo-second-order, Elovich and Intra-particle models were used to validate the kinetic models of the process. The pseudo-second-order and Elovich models were the best fitted kinetic model in this investigation. Thermodynamic parameters of the energy of gibes, the enthalpy, and the entropy were calculated. Generally, the adsorption process was distinguished as an exothermic and spontaneous.